Penggunaan Metode Al-Hira' dalam Mempercepat Membaca Al-Qur'an Anak Usia Dini di RA Yaa Bunayya - Beby Melati; Mukhlis Mukhlis; Zulpina Zulpina (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Beby Melati (NIM: 20030003) conducted research on "Using the Al-Hira Method in Accelerating Understanding of Al-Qur'an Reading in RA Yaa Bunayya, Mompang Julu Village, North Panyabungan District." This research aims to evaluate the effectiveness of the Al-Hira' method in improving the ability to read the Al-Qur'an in early childhood. The background is that there are still students who have difficulty reading the Al-Qur'an even though they have used the Iqra' method. The research method used is Classroom Action Research (PTK) using the Kemmis and McTanggart model. This research involved 10 children aged 5-6 years. The research results show that applying the Al-Hira' method can speed up the process of learning to read the Al-Qur'an. In cycle I, 50% of children showed development as expected, while in cycle II, 40% of children achieved very good development. Inhibiting factors in implementing this method include difficulties in distinguishing hijaiyah letters and students' lack of focus. Meanwhile, support from teachers and a conducive learning environment are supporting factors. In conclusion, the Al-Hira' method is effective in improving comprehension of reading the Al-Qur'an at RA Yaa Bunayya, making a significant contribution to early childhood education.